Development of a Patient Scheduling System for a Radio Diagnosis Department. Issue 3 (3rd July 2019) - Arun, P. P.; Panicker, Vinay V.
Abstract: Health care organizations worldwide are constantly under pressure to deliver quality services. Reducing the waiting time of patients is considered to be a significant issue in hospitals. In this study, a radio-diagnosis department in a healthcare organization is considered. The present study mainly focuses on the queuing system of a computed tomography scan section of a public hospital in South India. Simulation is used as an aid to study the behavior of the system. This article also contributes a Visual Basic with Applications based excel tool to tackle the need for a user-friendly tool for scheduling the patients.